A New Scoring System of Oral Lichen Planus - Chintada Suvarna; Priya Sivan Padma; Hashim Nada Tawfig; Mohammed Riham; Rahman Muhammed Mustahsen; Shetty Shishir Ram; Farghal Nancy Soliman; Alyami Jaber Sadan Hamad (Wolters Kluwer Medknow Publications, 2024)
Lichen planus (LP) is a chronic, immune-mediated mucocutaneous disorder increasingly becoming common in the general population with female predominance. Clinically, there are different forms of lichen planus with the presence of the main characteristic feature of Wickham striae. Literature, to date, is abundant with various scoring systems of oral lichen planus, and among them, the most commonly followed scoring system was the one proposed by the Thongprasom system because of its simplicity and ease of application.AimThe aim of the present study is to critically review all the disease scoring systems on oral lichen planus (OLP) that have been reported in the literature during the past decades. A systematic literature search was performed using PUBMED, MEDLINE, EMBASE, and COCHRANE Library with language restriction to English. The search was carried out incorporating the published literature from 1980 to 2020 using the MeSH (medical subject heading) terms. A literature search was done using keywords: Staging, Grading, Oral lichen planus, Diagnostic, and Therapeutic. Out of 25 publications, related to search strategy, 22 full articles, which were related to the disease scoring system for oral lichen planus, were acquired for further inspection. Out of the 22 articles, 15 articles met the inclusion criteria. The data was collected and a brief summary of the studies regarding the different disease scoring systems for oral lichen planus was explained. Taking into consideration, the parameters were not included in the previous disease scoring system. A new proposal encompassing a scoring system for oral lichen planus considering the missing parameters along with an amalgamation of histopathological criteria of dysplasia is presented. It also proposes to grade and stage the lesions and recommend appropriate therapy for each of such lesions.